Increasing Sporadic Covid-19 Cases:Should We Heed Airborne Transmission Of SARS-CoV-2? - Ahmad Mahfuz, Gazali (CodeBlue, 2021)
Clear guidance about the importance of moving activities outdoors, improving indoor air using ventilation and filtration, and improving protection for high-risk workers must be considered as public health measures.